The fibrogenic actions of the coagulant and plasminogen activation systems in pulmonary fibrosis. (April 2018) - Schuliga, Michael; Grainge, Christopher; Westall, Glen; Knight, Darryl
Graphical abstract: Highlights: The coagulation and plasminergic systems contribute to lung fibrosis in disease. Components of both systems evoke potent cell-mediated fibrogenic actions. Coagulant proteases ( ie FXa) contribute to lung fibrosis by activating PARs. Up-regulated uPAR contributes to the fibrogenic phenotype of lung fibroblasts in IPF. PAI-1 sensitizes alveolar epithelial cells to apoptosis by its binding to vitronectin. Abstract: Fibrosis causes irreversible damage to lung structure and function in restrictive lung diseases such as idiopathic pulmonary fibrosis (IPF). Extravascular coagulation involving fibrin formation in the intra-alveolar compartment is postulated to have a pivotal role in the development of pulmonary fibrosis, serving as a provisional matrix for migrating fibroblasts. Furthermore, proteases of the coagulation and plasminogen activation (plasminergic) systems that form and breakdown fibrin respectively directly contribute to pulmonary fibrosis. The coagulants, thrombin and factor Xa (FXa) evoke fibrogenic effects via cleavage of the N-terminus of protease-activated receptors (PARs). Whilst the formation and activity of plasmin, the principle plasminergic mediator is suppressed in the airspaces of patients with IPF, localized increases are likely to occur in the lung interstitium. Plasmin-evoked proteolytic activation of factor XII (FXII), matrix metalloproteases (MMPs) and latent, matrix-bound growth factors such as epidermal growth factor (EGF) indirectly implicate plasmin in pulmonary fibrosis. Another plasminergic protease, urokinase plasminogen activator (uPA) is associated with regions of fibrosis in the remodelled lung of IPF patients and elicits fibrogenic activity via binding its receptor (uPAR). Plasminogen activator inhibitor-1 (PAI-1) formed in the injured alveolar epithelium also contributes to pulmonary fibrosis in a manner that involves vitronectin binding. This review describes the mechanisms by which components of the two systems primarily involved in fibrin homeostasis contribute to interstitial fibrosis, with a particular focus on IPF. Selectively targeting the receptor-mediated mechanisms of coagulant and plasminergic proteases may limit pulmonary fibrosis, without the bleeding complications associated with conventional anti-coagulant and thrombolytic therapies.